Role of serum micro-RNA 486-5p in Egyptian cirrhotic hepatitis C patients with hepatocellular carcinoma - Amany N. Abbasy; Rasha Saeed; Mohamed M. El Shafei; Mohamed A. Abdel Aziz (SpringerOpen, 2024)
Abstract Background Hepatocellular carcinoma (HCC) is the prevailing primary liver tumor. To pick HCC at the initial stages is quite strenuous, despite the advent of serum biomarkers, mainly alpha-fetoprotein (AFP), to predict the development and progression of HCC. One proposed biomarker for the diagnosis of HCC is micro-RNA 486-5p (miRNA 486-5p). Hence, the current study was conducted to interrogate the role of miRNA 486-5p in the diagnosis of HCC in a cohort of Egyptian patients with hepatitis C virus (HCV) related liver cirrhosis (LC). This case-control study included twenty-five patients with HCC as studied cases and twenty-five patients with LC as controls. Patients in both groups were classified according to the Child-Pugh score. HCC patients were further classified according to the Barcelona Clinic Liver Cancer (BCLC) classification. Results MiRNA 486-5p was found to be statistically notably elevated in patients with HCC than in those with LC. It was found to significantly correlate with portal vein invasion. Conclusions Serum miRNA 486-5p could be a particularly sensitive biomarker in the diagnosis of HCC as well as prediction of portal vein invasion, as firmly advocated by this study.